Traduire vers la langue maternelle de l’autrice - Zupančič, Metka (Vestnik za tuje jezike, 2025)
The story L’Envahissement (L’Harmattan, 2020), by Metka Zupančič, was conceived in Canada in the late 1990s, doubtless in the context of the French and more largely Francophone feminist liter-ary trends of the time. Its publication in France not only coincided with the author’s return to her native Slovenia, but also with the rising interest in autofiction, which best defines the nature of this text. To provide readers with access to the book in Slovene, the author suggested its translation to Živa Čebulj. Published under the title Tisto neustavljivo (Hiša poezije, 2023), the translated book was subsequently often perceived by critics and general readers as written directly in Slovene, thus enabling a particular dialogue with contemporary Slovene women’s writing. Its quality was underscored by its inclusion among the finalists for the 2024 Charles Nodier Translation Award. The present article, focusing on translation theory issues and written jointly by the author and the translator of this work, takes into consideration the particular challenges of this process, which were resolved thanks to close collaboration between all parties involved, including the editor. After presenting the methodology used, and starting with the title, the article focuses on salient examples of the changes made in the translation. Subsequently, the analysis focuses on several significant changes to the lexical, syntactic, and semantic components that enabled the integration of this story into the target language context, while maintaining the specific characteristics of the original text, namely its intensity, its particular rhythm with predominantly long sentences and its transcultural positioning between origins and displacements, often linked to multiple intertextual references.
Keywords: authenticité; authenticity; autofiction; avtentičnost; avtofikcija; complicité; complicity; langue maternelle; materinščina; native tongue; prevajanje; soustvarjalnost; traduction; translation